Building climate resilience through diversifying crop-livestock systems: The Ukama-Ustawi Project - Tariro Gwandu; Mhlanga, Blessing; Thierfelder, Christian (Zimpapers, 2024)
Climate change continues to exert severe impacts on agriculture, particularly in Eastern and Southern Africa (ESA) including Zimbabwe. The challenges posed by higher temperatures, erratic rainfall patterns, delayed onset of the cropping season, and increased frequency of extreme weather events threaten the very foundation of agricultural productivity in the region. The impact is more severe for smallholder farmers particularly under rain fed systems. This year, Zimbabwe has witnessed the effects of the El-Niño-induced drought and the season has been so drastic that the Government declared it a national disaster.